Influence of individual adaptability and organizational factors on philanthropic behavior and mediating role of social network among community health workers, Malaysia - Alias, Siti Noormi (2016)
Philanthropic behavior of community health workers (CHWs) refers to individual action directed towards bridging the gap in health care provisions among underserved population without expecting monetary compensation in return. This study was conducted to determine the factors influencing philanthropic behavior with the existence of social network as a mediating variable. This study adopted quantitative research paradigm using correlational research methodology. The unit of analysis of this study is the individual CHW. Data were collected from 300 CHWs of MERCY Malaysia in which the data collection processes were fully administered by the management team of the organization due to protection issue of members’ personal information. Structural Equation Modeling was used in the analysis to test the structural model of the study. Results on the direct effect of the analysis showed that social network, emotional-oriented coping, social trust, informational justice and perceived organizational support significantly influenced philanthropic behavior. These results explained that active participants in the social network are exposed to extensive probability for philanthropic activities. Those who easily trust others will have the tendency to have philanthropic behavior. These individuals are considered as highly probable to contribute to community development. In addition, these CHWs tend to use emotions in resolving challenging situations in their daily life. Moreover, perceived informational justice and organizational support influenced CHWs’ commitment to continuously perform their voluntary work in healthcare. Findings from the SEM analysis indicated that task-oriented and avoidance-oriented coping, social trust, procedural justice and perceived organizational support indirectly influence philanthropic behavior through the mediating role of social network. The study concluded the important role of social network as a linking factor among these variables. Individuals who are lower in avoidance coping, and higher in task coping, social trust, procedural justice and perceived organizational support are more likely to have potent and extensive social network to enable them to have a vast informational exchange, consequently, inspired them to have interest in philanthropic behavior. These findings are in line with the notion of Social Network Theory in which social network makes contribution of individual adaptability and organizational factor to philanthropic behavior clearer. This study provides a support for the direction to Human Resource Development and Community Development practice as a new element based on Malaysian context. This study also supports the Theory of Planned Behavior, and Social Identity Theory (SIT) in emphasizing the important influence of individual adaptability and organizational factors on philanthropic behavior of CHWs.